Molecular Dynamics Investigation of gluazo, a Photo-Switchable Ligand for the Glutamate Receptor GluK2. - Yanan Guo; Tino Wolter; Tomáš Kubař; Martin Sumser; Dirk Trauner; Marcus Elstner (PLoS ONE, 2015)
Photochromic ligands (PCLs), defined as photoswitchable molecules that are able to endow native receptors with a sensitivity towards light, have become a promising photopharmacological tool for various applications in biology. In general, PCLs consist of a ligand of the target receptor covalently linked to an azobenzene, which can be reversibly switched between two configurations upon light illumination. Gluazo, as a PCL that targets excitatory amino acid receptors, in its dark-adapted trans iso-form was characterized to be a partial agonist of the kainate glutamate receptor GluK2. Application of UV light leads to the formation of the cis form, with remarkedly reduced affinity towards GluK2. The mechanism of the change of ligand affinity induced by the photoisomerization was unresolved. The presented computational study explains how the isomerization of such a PCL affects the structural changes in the target receptor that lead to its activation.